2015
DOI: 10.1021/acs.molpharmaceut.5b00541
|View full text |Cite
|
Sign up to set email alerts
|

Transepithelial Transport of PAMAM Dendrimers Across Isolated Human Intestinal Tissue

Abstract: Poly(amido amine) (PAMAM) dendrimers have shown transepithelial transport across intestinal epithelial barrier in rats and across Caco-2 cell monolayers. Caco-2 models innately lack mucous barriers, and rat isolated intestinal tissue has been shown to overestimate human permeability. This study is the first report of transport of PAMAM dendrimers across isolated human intestinal epithelium. It was observed that FITC labeled G4-NH2 and G3.5-COOH PAMAM dendrimers at 1 mM concentration do not have a statistically… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
8
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 61 publications
(174 reference statements)
2
8
0
Order By: Relevance
“…While we observed no difference in permeability between our groups ( Figure 1A), our low number of subjects coupled with the enormous heterogeneity observed in IBD prevents us from proving or disproving this hypothesis but the finding that P app of FD4 can be assessed consistently in multiple patient iPSC-derived lines in Transwell inserts confirms the technical feasibility of this approach and now permits an examination of this hypothesis by including a much larger number of subjects within each group. The basal P app of FD4 (0.57-0.92 × 10 −7 cm/s) compared favorably with human small intestine (0.5-2.1 × 10 −7 cm/s) recordings in Ussing chambers [33,34]. Additionally, our P app values along with our basal TEER values (404-615 Ω•cm 2 ; Figure 2B) also compared favorably to a recent study which reported a basal TEER of 420 Ω•cm 2 and P app value of 0.12 × 10 −6 cm/s using iPSC derived intestinal epithelial cell monolayers generated by CDX2 transduction [35].…”
Section: Discussionmentioning
confidence: 89%
“…While we observed no difference in permeability between our groups ( Figure 1A), our low number of subjects coupled with the enormous heterogeneity observed in IBD prevents us from proving or disproving this hypothesis but the finding that P app of FD4 can be assessed consistently in multiple patient iPSC-derived lines in Transwell inserts confirms the technical feasibility of this approach and now permits an examination of this hypothesis by including a much larger number of subjects within each group. The basal P app of FD4 (0.57-0.92 × 10 −7 cm/s) compared favorably with human small intestine (0.5-2.1 × 10 −7 cm/s) recordings in Ussing chambers [33,34]. Additionally, our P app values along with our basal TEER values (404-615 Ω•cm 2 ; Figure 2B) also compared favorably to a recent study which reported a basal TEER of 420 Ω•cm 2 and P app value of 0.12 × 10 −6 cm/s using iPSC derived intestinal epithelial cell monolayers generated by CDX2 transduction [35].…”
Section: Discussionmentioning
confidence: 89%
“…28,[43][44][45][46] In vivo models in comparison to Caco-2 cell monolayers comprise mucus layers, supportive mixed cell populations, and basement membrane. Furthermore, these models allow the comparison of differences in the segmental transport throughout different regions of the GI tract.…”
Section: Translocation Of Pamam Dendrimers Across Isolated Intestinalmentioning
confidence: 99%
“…The ability to predict the human intestinal permeability of PAMAM dendrimers based on results obtained from isolated human intestinal tissue was first reported by Dallin et al 44 Human jejunal and colonic tissues received from colectomy, pancreatic duodenectomy, and Roux-en-Y gastric bypass surgery patients. The permeability of PAMAM dendrimers was evaluated along with the penetration enhancing effects on the small paracellular marker mannitol.…”
Section: Translocation Of Pamam Dendrimers Across Isolated Intestinalmentioning
confidence: 99%
See 1 more Smart Citation
“…This has been clearly established using ethylenediaminetetraacetic acid (EDTA, Supplementary material Schema S1 ), a known Ca 2+ chelator, that has been shown to open and transverse the tight junctions ( Amsterdam & Jamieson, 1974 ). Several publications have suggested that PAMAM dendrimers also would be able to travel across the intestinal barrier using the same mechanism ( Hubbard, Ghandehari, & Brayden, 2014 ; Hubbard et al, 2015 ). Due to their anionic charge the carboxylic acid (COOH) terminated Generation 3.5 (G3.5) PAMAM dendrimers may be capable of chelating Ca 2+ in solution with a chelation efficiency similar to EDTA ( Noach et al, 1993 ).…”
Section: Introductionmentioning
confidence: 99%